Advertising for dummies: It is illegal under Indian law to export this book from India - Dahi, Gary (New Delhi Wiley India Pvt. Ltd., 2023)
So, you need to create an advertising campaign that brings in more customers, adds more dollars to your bottom line, and validates all the reasons you went into business in the first place. But how can you make your ad look and sound like champagne if your budget can only afford beer? Are you wasting your time trying to sell ice to an Eskimo? The world of advertising can seem like a daunting place-but it doesn't have to be